New records of three Aroids from Bangladesh - Ara, Hosne; Hassan, Md Abul (Bangladesh Journal of Plant Taxonomy, 2005)
Three species of Araceae viz. Colocasia oresbia A. Hay, Rhaphidophora grandis Schott and R. pertusa (Roxb.) Schott are recorded here for the first time from Bangladesh. Correct names with important synonyms, illustrated description, flowering and fruiting times, ecology, geographical distribution and occurrence within Bangladesh for each species are provided. Key words: Three new records, Araceae, Bangladesh DOI: 10.3329/bjpt.v12i1.610 Bangladesh J. Plant Taxon. 12(1): 25-32, 2005 (June)